2015
DOI: 10.3174/ajnr.a4393
|View full text |Cite
|
Sign up to set email alerts
|

Early Quantification of Hematoma Hounsfield Units on Noncontrast CT in Acute Intraventricular Hemorrhage Predicts Ventricular Clearance after Intraventricular Thrombolysis

Abstract: BACKGROUND AND PURPOSE: Thrombolytic efficacy of intraventricular rtPA for acute intraventricular hemorrhage may depend on hematoma composition. We assessed whether hematoma Hounsfield unit quantification informs intraventricular hemorrhage clearance after intraventricular rtPA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…2,6,25,34 Furthermore, the clearance of IVH with tissue plasminogen activator has been the target of ongoing studies. 11,12 Although qualitative scores (original and modified Fisher grade, 3 LeRoux score, 15 and original and modified Graeb scores 1,6,21 ) have been established for evaluating SAH and IVH, assessment of hemorrhage qualitatively can be inconsistent and imprecise. 27 A recent study positively correlated the radiodensity of intracerebral hemorrhage to perihemorrhagic edema, suggesting that radiodensity may play a role in evaluating brain irritation/injury and predict clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,6,25,34 Furthermore, the clearance of IVH with tissue plasminogen activator has been the target of ongoing studies. 11,12 Although qualitative scores (original and modified Fisher grade, 3 LeRoux score, 15 and original and modified Graeb scores 1,6,21 ) have been established for evaluating SAH and IVH, assessment of hemorrhage qualitatively can be inconsistent and imprecise. 27 A recent study positively correlated the radiodensity of intracerebral hemorrhage to perihemorrhagic edema, suggesting that radiodensity may play a role in evaluating brain irritation/injury and predict clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, elevated levels of several CSF proteins have been linked with poorer prognosis in aneurysmal SAH patients. 4,5,[9][10][11][16][17][18]22,24,26,28,29,33,38,39 This study had several limitations, including the small sample size and its retrospective nature. Moreover, the proposed method to calculate ventricular density involves manual selection of the ventricular system.…”
Section: Discussionmentioning
confidence: 99%
“…Further, Hounsfield units (HU) of the mass measured +60 HU, a density measurement supporting the diagnosis of a hematoma, with no mention of heterogeneous fluid. 7 Consultation by the plastic surgery service on hospital day 2 revealed a clinical picture consistent with OCS despite high-normal tonometry readings including vision changes, pain, proptosis, and total external ophthalmoplegia. The patient was taken to the operating room for a lateral canthotomy and cantholysis.…”
Section: Case Reportmentioning
confidence: 97%
“…Further, Hounsfield units (HU) of the mass measured +60 HU, a density measurement supporting the diagnosis of a hematoma, with no mention of heterogeneous fluid. 7…”
Section: Case Reportmentioning
confidence: 99%
“…72,73 At this time, individualized dosing for IVF has not been studied. Variations in response to IVF with alteplase is a subject of future research and has been identified in related cohorts with radiographic features 74 and clot-related factors. 75 Additionally, genetic factors modulating the response to intravenous alteplase for revascularization after acute ischemic stroke have been characterized, including Apo E2 phenyotype, 76 polymorphisms at loci of the factor XIII gene, 77 thrombin-activatable fibrinolysis inhibitor gene, 78 interleukin 1B gene, and von Willebrand factor genes.…”
Section: Enhancing Clot Lysis and Removalmentioning
confidence: 99%